Recombinant receptor-binding motif of spike COVID-19 vaccine candidate induces SARS-CoV-2 neutralizing antibody response - Hossein Samiei-Abianeh; Shahram Nazarian; Emad Kordbacheh; Alireza Felegary (BioImpacts)
Introduction: The SARS-CoV-2 pandemic necessitates effective therapeutic solutions. The receptor-binding motif (RBM) is a subdomain of the spike protein's receptor-binding domain (RBD) and is critical for facilitating the binding of SARS-CoV-2 to the human ACE2 receptor. This study investigates the use of the receptor-binding motif (RBM) domain as an immunogen to produce potent neutralizing antibodies against SARS-CoV-2. Methods: The RBM gene was codon-optimized and cloned into the pET17b vector for expression in E. coli BL21 (DE3) cells, induced with 1 mM IPTG. The recombinant RBM protein was purified using Ni-NTA affinity chromatography. After validating the recombinant RBM by Western blotting with anti-His tag antibodies, BALB/c mice were immunized with 20 µg of the purified RBM protein. Anti-RBM IgG was subsequently purified using protein G resin, and its neutralizing capacity was assessed using the Pishtaz Teb Zaman Neutralization Assay Kit. Results: The recombinant RBM protein, with a molecular weight of 10 kDa, was expressed as inclusion bodies. the typical yield of purification was 27 mg/L of bacterial culture. The neutralization test demonstrated a concentration of 36 µg/mL of neutralizing antibodies in the immunized serum, preventing the spike protein from binding to ACE2. Conclusion: Our study demonstrated that anti-RBM antibodies exhibited neutralization effects on SARS-CoV-2. These findings provide evidence for the development of a vaccine candidate through the induction of antibodies against the RBM, necessitating further studies with adjuvants suitable for human use to evaluate its potential for human vaccination.